Investigation of rebar corrosion in plain and steel fiber reinforced concrete under static and dynamic loading - Niş, Anıl. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Reinforcement corrosion is one of the most important causes of deterioration for concrete structures. In codes and standards, there are recommendations for protection against reinforcement corrosion. In the European and Turkish standards (TS EN206 and TS ENV 1992), these recommendations are based on the protection of the steel reinforcement by limiting the access of aggressive agents. Concrete cover thickness and quality are increased in more aggressive environmental conditions to assure the required lifetime for the structure. However, the cracking of the concrete is not taken into consideration in lifetime estimations. Concrete is a brittle material that can be easily cracked due to several factors. The role of cracks in reinforcement corrosion is controversial. According to the ACI 318-08 and ACI 224R-01, more important parameters are concrete cover and concrete quality as the corrosion may localize despite an earlier onset. In ACI 224R-01, the importance of cyclic loading is emphasized as it can cause an increase in crack width and thus in corrosion. In the present study, the role of cracks on reinforcement corrosion was investigated. Concrete cover and quality recommended by standards were tested for cracked concrete. Cracks obtained under specified flexural loads that were applied on the prismatic specimens were compared for plain and steel fiber reinforced concretes. Obtained results were used for the evaluation of the limits recommended by the standards. Results showed the importance of waterto- cement ratio even in the presence of the cracks. Corrosion rate was found to increase by increasing crack width which is in corresponding order, specimens cracked under dynamic load, specimens cracked under static load, uncracked specimens. Steel fiber use decreased corrosion rate results when water-to-cement ratio was low.
Keywords: Reinforced concrete construction.; Safety factor in engineering.